Performance Measurement for Interactive Multi-objective Evolutionary Algorithms - Long Nguyen; Hung Nguyen Xuan; Lam Thu Bui (2015 Seventh International Conference on Knowledge and Systems Engineering (KSE), 2015)
This paper suggests to use a different metric for performance of multiple-point interactive evolutionary multi-objective algorithms. We defined a preferred region based on a set of user's reference points. Based on the preferred region, we also define a User based Front (UbF) which is generated from the preferred region. UbF is used in calculation of Generational Distance (GD) and Inverse Generational Distance (IGD). The usage of the metric in experiments indicated meaningful comparisons for interactive multi-objective evolutionary algorithms using multiple reference points.